Notes on Technic: A simple procedure for autoradiography of keratinocyte cultures - Conti, Claudio J.; Aldaz, Claudio M.; Giménez, Irma B. (The Williams & Wilkins Co., 1982)
Fil: Conti, Claudio J. Comisión Nacional de Energía Atómica; Argentina